Carbon sphere@Co9S8 yolk-shell structure with good morphology stability for improved lithium storage performance. (22nd August 2017) - Tang, Xuekun; Huang, Jing; Feng, Qiming; Liu, Kun; Luo, Xianping; Li, Zishun
Abstract: The poor electronic conductivity and huge volume expansion of cobalt sulfides upon cycling would lead to their poor electrochemical performances for Lithium-ion batteries. Here, we rationally design a yolk-shell carbon sphere@Co9 S8 (C@CS) composite, which demonstrates improved kinetics and excellent morphology stability during cycling. This structure can keep Co9 S8 shell from collapse and aggregation. After cycling, a layer of thin solid electrolyte interphase is coated on the Co9 S8 shells and prevented them from dissolving in electrolyte, which is helpful for the electrochemical performances. As a result, the C@CS electrodes exhibit good lithium storage performances, including excellent cyclic stability up to 300 cycles at 1000 and 2000 mA g −1 and high-rate property of 4000 mA g −1 with a capacity of 489 mA h g −1 .